Framework E-Auction Berbasis Syariah Untuk Membangun Kepercayaan Konsumen Dalam Menggunakan Sistem Lelang - Reski Mai Candra; Novriyanto Novriyanto (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
E-auction bidding process designed to achieve a transparent, efficient, effective and integrated. e-Bay.com one example of a site that uses the e-auction system. Using the models of e-Commerce Consumer to consumer-type C2C (Consumer-to-Consumer), eBay.com create a market space where consumers can auction off or sell goods directly to other consumers. It can get a problem that is not in accordance with the principles of Islamic law, because there are an element of manipulation, collusion or other foul play, and there are features that are prohibited such as riba (interest), gambling (gambling) or gharar (uncertainty). To overcome the problem that does not comply with the rules of Sharia, and then designed a framework of sharia-based e-auction that could overcome the problems occurred. So that consumers trust and want to use sharia-based e-auction, then the thing to note is a belief that can increase of confidence and desire. Results from this study, it can generate four factors that Affect the level of trust buyers, verification of proof of trust auctions, trust in the auction price certainty and confidence in the certificates.